Influence of organic modification on mechanical properties of melt processed intercalated poly(methyl methacrylate)-organoclay nanocomposites - Tiwari, Rajkiran R.; Natarajan, Upendra (Journal of Applied Polymer Science, 2007)
The influence of organic modifiers on intercalation extent, structure, thermal and mechanical properties of poly(methyl methacrylate) (PMMA)-clay nanocomposites were studied. Two different organic modifiers with varying hydrophobicity (single tallow versus ditallow) were investigated. The nanocomposites were prepared from melt processing method and characterized using wide angle X-ray diffraction, transmission electron microscopy, thermogravimetric analysis, differential scanning calorimetry (DSC), and tensile tests. Mechanical properties such as tensile modulus (E), break stress (sigma(brk)), and 0% break strain (epsilon(brk)) were determined for nanocomposites at various clay loadings. Extent of PMMA intercalation is sufficient and in the range 9-15 angstrom depending on organoclay and filler loading. Overall thermal stability of nanocomposites increases by 16-30 degrees C. The enhancement in T-g of nanocomposite is merely by 2-4 degrees C. With increase in clay loading, tensile modulus increases linearly while % break strain decreases. Break stress is found to increase till 4 wt % and further decreases at higher clay loadings. The overall improvement in thermal and mechanical properties was higher for the organoclay containing organic modifier with lower hydrophobicity and single tallow amine chemical structure. (c) 2007 Wiley Periodicals, Inc.
Keywords: mechanical properties; Nanocomposites; organoclay; structure; Thermal properties